How Indonesia and Thailand Transform International Law: A Study of Access and Benefit Sharing - Kusniati, Retno (Faculty of Law, Universitas Jambi, 2024)
This paper addresses the transformation of international law, The Convention on Biological Diversity (CBD) and its Nagoya Protocol on Access and Benefit Sharing (NP), into national law. Those convention and protocol have established an Access and Benefit Sharing (ABS) system between utilizers and providers of genetic resources, including for indigenous people. One of the objectives of treaties it to obligate States to make law to ensure the rights of indigenous people for benefit sharing. Indonesia and Thailand are megadiversity countries and also the parties of the treaties. This paper tries to compare Indonesia and Thailand in transforming the ABS law into their national legal system and how the judges in Indonesia and Thailand use international treaty in deciding the cases. CBD is the starting point of the ABS concept for legal rights or interests that can be owned in relation to genetic resources. In this sense ABS is one of the new and innovative legal concepts introduced in international law. However, the CBD has only created a concept of ABS rights policy. Therefore, the concept of ABS rights of indigenous peoples needs to be formulated in national law by enacted the rights of indigenous peoples related to genetic resources.